The Relationship Between Hedonism Lifestyle and Student Consumer Behavior in Pamekasan District - Fadali, Fadali Rahman; Dera Damayanti; Dwi, Dwi Indah Ria Astari; Ilmi, Yulia Ilmi Qur'ani; Istianah, Mohammad Raihan Alghifari; Raihan, Istianah Asas (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2026)
Technological developments and globalization have encouraged the emergence of a hedonistic lifestyle among college students, characterized by a tendency to pursue pleasure, luxury, and trend-driven consumption. This situation has the potential to influence student consumer behavior, including excessive purchasing and a lack of consideration for real needs. This study aims to analyze the relationship between a hedonistic lifestyle and student consumer behavior in Pamekasan Regency. The study used a quantitative approach with a correlational approach. The sample consisted of 104 students selected through purposive sampling. Data collection was conducted through an online questionnaire with a Likert scale. Validity tests using Pearson Product Moment correlation showed all items were valid, while reliability tests yielded a Cronbach's Alpha value of 0.956, indicating high reliability of the instrument. Normality tests showed the data were normally distributed (sig. X = 0.080; Y = 0.070). Spearman's Rho correlation test yielded a coefficient value of 0.780 with a significance level of 0.000. The results of this study indicate a strong, positive, and significant relationship between a hedonistic lifestyle and student consumer behavior. This means that the higher the level of hedonism in students, the higher their tendency to engage in consumer behavior. Therefore, a hedonistic lifestyle is a significant factor influencing student consumption patterns in Pamekasan Regency. This study concluded that the higher the level of hedonism in students, the higher their tendency to engage in consumer behavior. These findings are expected to serve as a guide for universities, parents, and students in understanding and managing consumption patterns to be more rational and based on priority needs.